PENGARUH KONFLIK PERAN DAN STRES KERJA TERHADAP KOMITMEN ORGANISASI DI RUMAH SAKIT Tk IV SALAK, BOGOR - Sri Rulestri L.H.; Henry Eryanto (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
ABSTRACTThe study aims to determine whether there is effect role conflict and work stress to organization commitment at Rumah Sakit Tk IV Salak Bogor and also to get a valid and reliable data or fact, to prove it. The research has been done during April 2013. The method of this research is survey. The population research was all nurse of Rumah Sakit Tk IV Salak Bogor as much as 110 nurses. And the sample used as many 40 married women nurses by using simple random sampling. The result reveals that there is effect between role conflict to organization commitment, and also work stress to organiza-tion commitment, and then there is effect between role conflict and work stress to organization commitment of nurses Rumah Sakit Tk IV Salak, Bogor.Keywords:role conflict,work stress, organization commitment